Workshop Kreatifitas Guru Bidang Studi Madrasah Ibtidaiyah Menuju Pembelajaran Berbasis Digital di MI Assa’adah Bungah Gresik - Alimin; Wardani, Happy Kusuma; Hidayah, Bariqotul; Ainiyah, Maslakhatul (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
The role of teachers in the learning process remains indispensable despite the advancements in digital technology. While artificial intelligence has taken over many aspects of human work, the presence of teachers is irreplaceable, especially at the elementary school level, where students need visual and auditory stimulation that only teachers can provide. The rapid changes in learning targets necessitate continuous updates in teachers' digital technology knowledge to maintain their relevance and effectiveness. In the digital era, the educational environment, particularly in madrasah institutions, faces unique challenges as these institutions are often secondary choices for the public. Teachers in madrasahs play a fundamental role in character development during the early educational stages. However, the quality of education is heavily influenced by the teachers' ability to create digital learning media. Conventional teaching methods starkly contrast with modern systems that leverage technology for learning. This article highlights the necessity for teachers to develop digital learning media, such as videos, to enhance student engagement and motivation. Despite students' enthusiasm for digital media, many madrasah teachers struggle with creating such content. Therefore, a special program, "WORKSHOP KREATIFITAS GURU BIDANG STUDI MADRASAH IBTIDAIYAH MENUJU PEMBELAJARAN BERBASIS DIGITAL DI MI ASSA’ADAH BUNGAH GRESIK," was implemented to address these challenges. Through several stages, the outcome of this workshop was successful, with teachers gaining new skills in digital media creation, leading to a more engaging and effective learning environment. The initiative also motivated further development and adoption of digital teaching methods among educators.